Knowledge and awareness of breast cancer among undergraduate students of Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam / Nurul Naimah Abd Salim - Abd Salim, Nurul Naimah (2014)
Cancer is a type of disease that act on cell and cause the cell to grow abnormally. Breast cancer is the primary causes of death of women worldwide. This study was done to identify the knowledge and awareness of breast cancer among faculty pharmacy students in Uitm Puncak Alam. A cross sectional study has been done involved 264 respondents. Data was collected by using self-administered questionnaire which includes questions on demographic data, awareness and knowledge of breast cancer. In this study, data were analysed by using Statistical Package for Social Science (SPSS) version 17 which include descriptive analysis and chi square test was used. Data analysis revealed that the respondents were females 67.3 % and males 33.7 % with range of ages from 19-21 years old 47.7 %, 22-24 years old 47.7 % and more than 25 years old 4.5 % . Out of 264 respondents, majority 262 know about breast cancer and indicated media (television, radio and internet) as sources of information with 88.6 %. However, majority of students do not kow the age to start practising breast self-examination and mammography. While for knowledge of breast cancer, most of respondents know about symptoms, breast cancer examination, risk factors and how to prevent breast cancer. This showed that students have knowledge about breast cancer but moderate awareness on breast cancer.